Incidence, treatments, and outcomes of SARS-CoV-2 and HIV co-infections - Rini Chaturvedi; Sumit Malhotra; Amit Sharma (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background We investigated the global threat of co-infection of severe acute respiratory coronavirus 2 (SARS-CoV-2) to patients living with another prevalent viral infection HIV. We have analyzed symptom status, treatment, and outcome of co-infected individuals. # Methods An extensive literature search of PubMed, preprint databases (bioRxiv, medRxiv, and preprints), and ClinicalTrials.gov was conducted from 1 December 2019 to 28 February 2021. Ninety-two potential studies involving 39,461 HIV and SARS-CoV-2 co-infected patients were analyzed with details of severity, their treatment, and the outcomes. # Results A total of 39,461 cases of people living with HIV have reported co-infection with SARS-CoV-2 worldwide. Of these coinfected individuals, the symptom status for 3,213 patients (~8%) was available, out of which 44% were severely/critically ill. The collated data show the fatality rate for human immunodeficiency virus (HIV) and SARS-CoV-2 coinfection to be 2.4% and a large proportion was found to have several comorbidities. The most commonly administered antiretroviral therapy to the people living with HIV was tenofovir/emtricitabine; these drugs are already in phase 3 clinical trials for coronavirus disease 2019 (COVID-19). We observed that majority of co-infected patients who survived were those on tenofovir/emtricitabine combination drug therapy for HIV. # Conclusions The current study demonstrates that patients with HIV may have worse outcomes due to COVID-19 than the general population. However, the HIV/SARS-CoV-2 coinfection needs to be analyzed across multiple countries with a high burden of HIV, and with a much larger cohort to gain a better understanding of the impact of SARS-CoV-2 on people living with HIV.